2016
DOI: 10.18805/ijar.v0iof.6820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan coating and rosemary oil on rainbow trout (Oncorhynchus mykiss, W. 1792) filets

Abstract: This study was performed to examine the effect of chitosan and rosemary oil on the shelf life changes of the rainbow trout filet. The samples divided into 4 groups. The control (I) group samples nothing were applied. The group II samples were applied solution of 2% chitosan. The group III samples were applied 2% chitosan and 0.05% rosemary oil and group IV samples only 0.05% rosemary oil. The samples of all groups storage at +4 °C for day 20. The microbiological (total mesophilemesophiles aerobe bacteria, H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the previous study, Ozogul and Özogul () reported that TVBN values in fish (rainbow trout) that was wrapped in aluminum foil and stored at 4–6 °C were found to be slightly higher than 20 mg/100 g (in the ninth day). TVBN value of the rainbow trout samples treated with chitosan solution (2%) was defined as 20.1 mg/100 g (in the ninth day) (Can & Patır, ). Different applications of chitosan on fish fillets such as dipping and spraying can delay the chemical deterioration during the cold storage, but the used concentrations of chitosan (0.5% and 1.0%) in these studies conducted by Augustini and Sedjati () and Alak () are highly higher than that of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, Ozogul and Özogul () reported that TVBN values in fish (rainbow trout) that was wrapped in aluminum foil and stored at 4–6 °C were found to be slightly higher than 20 mg/100 g (in the ninth day). TVBN value of the rainbow trout samples treated with chitosan solution (2%) was defined as 20.1 mg/100 g (in the ninth day) (Can & Patır, ). Different applications of chitosan on fish fillets such as dipping and spraying can delay the chemical deterioration during the cold storage, but the used concentrations of chitosan (0.5% and 1.0%) in these studies conducted by Augustini and Sedjati () and Alak () are highly higher than that of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Combined action of essential oils and chitosan may lead to synergistic effects. Rosemary oil containing chitosan coating on rainbow trout fillets exhibits more pronounced antibacterial and antioxidant effect than these components separately [61]. Chitosan coating containing eucalyptus essential oil and α-tocopherol prolongs the shelf life and reduces fat oxidation of fresh silver carp, which is more related to the combined presence of chitosan and eucalyptus oil than α-tocopherol used as an regular antioxidant food additive [62].…”
Section: Chitosan Applications For Food Shelf Life Prolongationmentioning
confidence: 99%